Addressing the Global Environmental Crisis: The Critical Role of Natural Science in Sustainable Solutions - Siyamsih, Dwi; Faradina, Anggia; Simpen, I Nengah; Noviya, Anis; Tasya, Amalia (PT. Anagata Sembagi Education, 2025)
This research aims to examine the role of natural sciences in overcoming global environmental crises through sustainable science-based solutions. With environmental problems such as climate change, pollution, and ecosystem degradation on the rise, a comprehensive scientific approach is needed to identify effective mitigation and adaptation strategies. The research method used in this article is Systematic Literature Review (SLR). This approach is used to collect and analyze previous research that discusses the contribution of natural sciences in dealing with environmental crises. The literature analyzed includes international journals, academic books, and research reports from trusted institutions. The data are categorized based on relevance, methods, results, and conclusions of the research to gain a deep understanding of the latest developments in sustainable solutions. The results of the study show that natural sciences have a crucial role in overcoming the global environmental crisis through various innovations and science-based approaches. Continuous research has contributed to the development of solutions such as renewable energy, environmental conservation, and environmentally friendly technologies. To increase the effectiveness of the implementation of these solutions, closer collaboration between scientists, governments, industry, and the public is needed in integrating research results into real policies and practices. Thus, increasingly complex environmental challenges can be overcome more effectively, so that the future of the earth can be better preserved for future generations.